Changing Expectations for the K-12 Teacher Workforce: Policies, Preservice Education, Professional Development, and the Workplace - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Teachers play a critical role in the success of their students, both academically and in regard to long term outcomes such as higher education participation and economic attainment. Expectations for teachers are increasing due to changing learning standards and a rapidly diversifying student population. At the same time, there are perceptions that the teaching workforce may be shifting toward a younger and less experienced demographic. These actual and perceived changes raise important questions about the ways teacher education may need to evolve in order to ensure that educators are able to meet the needs of students and provide them with classroom experiences that will put them on the path to future success. Changing Expectations for the K-12 Teacher Workforce: Policies, Preservice Education, Professional Development, and the Workplace explores the impact of the changing landscape of K-12 education and the potential for expansion of effective models, programs, and practices for teacher education. This report explores factors that contribute to understanding the current teacher workforce, changing expectations for teaching and learning, trends and developments in the teacher labor market, preservice teacher education, and opportunities for learning in the workplace and in-service professional development.
Keywords: Education

Location Data in the Context of Public Health, Research, and Law Enforcement: An Exploration of Governance Frameworks: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On June 8-9, 2022, an ad hoc planning committee under the auspices of the National Academies of Sciences, Engineering, and Medicine's Committee on Science, Technology, and Law hosted a workshop, Location Data in the Context of Public Health, Research, and Law Enforcement: An Exploration of Governance Frameworks. The workshop examined the collection, interpretation, and use of location data by government, academia, and industry. This publication summarizes the presentations and discussion of the workshop.
Keywords: Computers and Information Technology

Frameworks for Higher Education in Homeland Security - National Research Council (The National Academies Press, 2005)
This report explores whether there are core pedagogical and skill-based homeland security program needs; examines current and proposed education programs focusing on various aspects of homeland security; comments on the possible parallels between homeland security, area studies, international relations, and science policy, as developed or emerging academic thrusts; and suggests potential curricula needs, particularly those that involve interdisciplinary aspects. The report concentrates almost exclusively on coursework-related offerings, primarily at the undergraduate and graduate levels.
Keywords: Behavioral and Social Sciences

Optimizing the Nation's Investment in Academic Research: A New Regulatory Framework for the 21st Century - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Research universities are critical contributors to our national research enterprise. They are the principal source of a world-class labor force and fundamental discoveries that enhance our lives and the lives of others around the world. These institutions help to create an educated citizenry capable of making informed and crucial choices as participants in a democratic society. However many are concerned that the unintended cumulative effect of federal regulations undercuts the productivity of the research enterprise and diminishes the return on the federal investment in research. Optimizing the Nation's Investment in Academic Research reviews the regulatory framework as it currently exists, considers specific regulations that have placed undue and often unanticipated burdens on the research enterprise, and reassesses the process by which these regulations are created, reviewed, and retired. This review is critical to strengthen the partnership between the federal government and research institutions, to maximize the creation of new knowledge and products, to provide for the effective training and education of the next generation of scholars and workers, and to optimize the return on the federal investment in research for the benefit of the American people.
Keywords: Policy for Science and Technology; Education

Developing a Framework for Measuring Community Resilience: Summary of a Workshop - National Research Council (The National Academies Press, 2015)
The 2012 National Research Council report Disaster Resilience: A National Imperative highlighted the challenges of increasing national resilience in the United States. One finding of the report was that "without numerical means of assessing resilience, it would be impossible to identify the priority needs for improvement, to monitor changes, to show that resilience had improved, or to compare the benefits of increasing resilience with the associated costs." Although measuring resilience is a challenge, metrics and indicators to evaluate progress, and the data necessary to establish the metric, are critical for helping communities to clarify and formalize what the concept of resilience means for them, and to support efforts to develop and prioritize resilience investments. One of the recommendations from the 2012 report stated that government entities at federal, state, and local levels and professional organizations should partner to help develop a framework for communities to adapt to their circumstances and begin to track their progress toward increasing resilience. To build upon this recommendation and begin to help communities formulate such a framework, the Resilient America Roundtable of the National Academies convened the workshop Measures of Community Resilience: From Lessons Learned to Lessons Applied on September 5, 2014 in Washington, D.C. The workshop's overarching objective was to begin to develop a framework of measures and indicators that could support community efforts to increase their resilience. The framework will be further developed through feedback and testing in pilot and other partner communities that are working with the Resilient America Roundtable. This report is a summary of the one-day workshop, which consisted of a keynote address and two panel sessions in the morning and afternoon breakout sessions that began the discussion on how to develop a framework of resilience measures.
Keywords: Conflict and Security Issues; Policy for Science and Technology; Earth Sciences

Monitoring International Labor Standards: National Legal Frameworks: Summary of a Workshop - National Research Council (The National Academies Press, 2003)
The National Research Council has convened the Committee on Monitoring International Labor Standards to provide expert, science-based advice on monitoring compliance with international labor standards. The committee has undertaken a two-year project with multiple intersecting activities.The committee is charged with assembling information on country compliance with international labor standards and organizing these data into an easily accessible, web-based format for use by the DOL. As one step in this process, a workshop in November 2002 was held to discuss national legal frameworks and the challenges of measuring the extent to which international standards have been incorporated into national laws and practices. Monitoring International Labor Standards is the summary of that workshop. This report communicates the key ideas and themes that emerged from the workshop presentations and discussions.
Keywords: Industry and Labor

The Future of Personal Transport in China: Summary of a Symposium, January 12, 2001 - National Research Council (The National Academies Press, 2001)
In August 1999 a delegation from the Chinese Academy of Engineering (CAE) visited The National Academies in Washington to discuss opportunities for collaboration on a study of the future of personal use vehicles in China. Barely motorized at present, China is confronted with the prospect of a massive increase in demand for automobiles. This is a summary of the first meeting of the Committee on the Future of Personal Use Vehicles in China, where the committee invited a group of experts to join some members of the committee to review the issues surrounding rapid motorization in China and the world experience in confronting similar problems in other countries. This symposium was designed to serve as the initial technical presentation to the committee and enabled some of the more difficult issues to be introduced by non-member experts in a setting outside of the committee room where they would be debated.

Strengthening Equitable Community Resilience: Criteria and Guiding Principles for the Gulf Research Program's Enhancing Community Resilience (EnCoRe) Initiative - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The Gulf Research Program of the National Academies of Sciences, Engineering, and Medicine has developed a program to strengthen community resilience, the Enhancing Community Resilience (EnCoRe) initiative. EnCoRe aims to reduce inequities in health and community resilience; advance research and practice in health and community resilience; and build the capacity of communities for addressing the impacts of climate change and disasters on at-risk populations. To achieve these goals, EnCoRe will support long-term, multiyear community engagement projects that partner directly with select communities across the Gulf region and Alaska. This report develops findings and recommendations intended to help guide EnCoRe in identifying, selecting, and engaging with communities as it moves forward with the initiative. Strengthening Equitable Community Resilience examines past and current community engagement efforts and other relevant materials, particularly those that have included communities in the Gulf region and Alaska, for the purpose of identifying guiding principles and lessons learned and then develops a set of guiding principles to identify criteria for selecting the participating communities in the EnCoRe program.
Keywords: Environment and Environmental Studies; Policy for Science and Technology

Evaluating the Effectiveness of Interventions to Prevent and Address Sexual Harassment: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Rising awareness of and increased attention to sexual harassment has resulted in momentum to implement sexual harassment prevention efforts in higher education institutions. Work on preventing sexual harassment is an area that has recently garnered a lot of attention, especially around education and programs that go beyond the standard anti-sexual harassment trainings often used to comply with legal requirements. On April 20-21, 2021, the National Academies of Sciences, Engineering, and Medicine hosted the workshop Developing Evaluation Metrics for Sexual Harassment Prevention Efforts. The workshop explored approaches and strategies for evaluating and measuring the effectiveness of sexual harassment interventions being implemented at higher education institutions and research and training sites, in order to assist institutions in transforming promising ideas into evidence-based best practices. Workshop participants also addressed methods, metrics, and measures that could be used to evaluate sexual harassment prevention efforts that lead to change in the organizational climate and culture and/or a change in behavior among community members. This publication summarizes the presentations and discussion of the workshop.
Keywords: Policy for Science and Technology

Developing a National STEM Workforce Strategy: A Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The future competitiveness of the United States in an increasingly interconnected global economy depends on the nation fostering a workforce with strong capabilities and skills in science, technology, engineering, and mathematics (STEM). STEM knowledge and skills enable both individual opportunity and national competitiveness, and the nation needs to develop ways of ensuring access to high-quality education and training experiences for all students at all levels and for all workers at all career stages.
Keywords: Education

Review of the SBIR and STTR Programs at the Department of Energy - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Since its founding in 1982, the Small Business Innovation Research (SBIR) program has become the largest and most comprehensive public research and development funding program of small business research in the United States. An underlying tenet of the SBIR program, and the related Small Business Technology Transfer (STTR) program, is that small and young firms are an important source of new ideas that provide the underlying basis for technological innovation, productivity increases, and subsequent economic growth. By involving qualified small businesses in the nation's research and development efforts, SBIR/STTR grants stimulate the development of innovative technologies and help federal agencies achieve their missions and objectives. At the request of the Department of Energy (DOE), this report examines the SBIR and STTR programs at DOE, focusing on the effectiveness of DOE's SBIR/STTR processes and procedures on topic and awardee selection; DOE outreach efforts to SBIR and STTR applicants; collaborations created between small businesses and research institutions on account of the programs; a range of direct economic and non-economic impacts to awardees; and the role of SBIR/STTR programs in stimulating technological innovation and contributing to DOE's research and development needs, whether directly from awardees or indirectly through spillovers from other firms.
Keywords: Industry and Labor

Strategic Innovation and Commercialization: Supporting IP and Tech Transfer to Advance U.S. Research Competitiveness: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
On February 7-8, 2023, the Government-University-Industry Research Roundtable of the National Academies of Science, Engineering, and Medicine convened a workshop for its membership and invited guests to discuss how to foster the health and productivity of the U.S. research enterprise in the context of challenges and potential solutions driven by new partnerships and other opportunities related to economic security and competition. The workshop considered critical elements to promote and strengthen research commercialization, including new protection and security frameworks for intellectual property, advancement of U.S. leadership in international standards organizations, and best practices to promote technology transfer. This publication summarizes the presentations and discussion of the workshop.
Keywords: Policy for Science and Technology

Sustainability and the U.S. EPA - National Research Council (The National Academies Press, 2011)
Sustainability is based on a simple and long-recognized factual premise: Everything that humans require for their survival and well-being depends, directly or indirectly, on the natural environment. The environment provides the air we breathe, the water we drink, and the food we eat. Recognizing the importance of sustainability to its work, the U.S. Environmental Protection Agency (EPA) has been working to create programs and applications in a variety of areas to better incorporate sustainability into decision-making at the agency. To further strengthen the scientific basis for sustainability as it applies to human health and environmental protection, the EPA asked the National Research Council (NRC) to provide a framework for incorporating sustainability into the EPA's principles and decision-making.
Keywords: Environment and Environmental Studies; Policy for Science and Technology

Advancing Economic Development and Workforce Readiness in Micropolitan Areas: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Micropolitan areas of the United States, cities with populations between 10,000 and 50,000 people, have received little attention from either the research or policy communities regarding their roles in the U.S. economy. Only recently has attention turned toward small-town America in order to try to characterize and understand the roles micropolitan areas play in productivity, growth, employment and, more broadly, in the innovation system of the nation. Likewise, little research has been undertaken to gain a better understanding of which policy instruments and frameworks can best support economic development and workforce readiness in micropolitan areas.
Keywords: Industry and Labor

Nuclear Proliferation and Arms Control Monitoring, Detection, and Verification: A National Security Priority: Interim Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
At the request of Congress, this report presents findings and recommendations related to governance of the U.S. government's monitoring, detection, and verification (MDV) enterprise and offers findings and recommendations related to technical MDV capabilities and research, development, test, and evaluation efforts, focused in particular on the nuclear fuel cycle, nuclear test explosions, and arms control.
Keywords: Conflict and Security Issues

Cleaning Up Sites Contaminated with Radioactive Materials: International Workshop Proceedings - National Research Council (The National Academies Press, 2009)
This publication features papers presented at the Workshop on Cleaning Up Sites Contaminated with Radioactive Materials, held in Moscow in June 2007. This activity was organized by the National Academies in cooperation with the Russian Academy of Sciences and with funding provided by the Russell Family Foundation. The workshop was designed to promote exchanges of information on specific contaminated sites in Russia and elsewhere and to stimulate greater attention to the severity of the problems and the urgent need to clean up sites of concern to the local and international communities.
Keywords: Environment and Environmental Studies

Attacks on Scientists and Health Professionals During the Pandemic: Proceedings of a Symposium—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Scientists and health professionals have long been targeted in connection with their professional work. Though this problem preceded the pandemic, it has emerged as a major concern, both in the United States and globally, as a result of COVID-19. Since the onset of the pandemic, scientists and health professionals have been subjected to threats and other attacks - online and offline - resulting from their efforts to combat the spread of COVID-19 with public health interventions and information. Reports of violence - carried out by numerous actors, including governments, groups, and individuals - are wide ranging and have come from all over the globe. In some cases, scientists, health professionals, and other groups have been targeted by multiple sources simultaneously, putting them at heightened risk of harm. Beginning September 1, 2022, the U.S. National Academies of Sciences, Engineering, and Medicine Committee on Human Rights hosted five webcasts examining the global problem of COVID-19-related attacks on researchers and health professionals, along with concerns regarding repression of information during the pandemic and implications for internationally protected rights. Topics included the targeting of scientists and public health professionals for providing evidence-based health information, global patterns of violence against health personnel, censorship and the right to information, science communication and human rights amid public health emergencies, and constructing a human rights framework for online health-related speech. This Proceedings of a Symposium-in Brief provides a high-level summary of the issues discussed during the series.
Keywords: Policy for Science and Technology

Roots and Trajectories of Violent Extremism and Terrorism: A Cooperative Program of the U.S. National Academy of Sciences and the Russian Academy of Sciences (1995-2020) - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
During the past 25 years, the U.S. National Academies of Sciences, Engineering, and Medicine, in collaboration with the Russian Academy of Sciences, have carried out a wide variety of activities to improve understanding of the challenges in containing and reducing ethnic conflicts, violent extremism, and terrorism. Roots and Trajectories of Violent Extremism and Terrorism provides an overview of this cross-ocean program, which has involved American and Russian scientists, engineers, and medical professionals from a large number of government agencies, leading research institutions, think tanks, educational institutions, analytical centers, and consulting and commercial firms in the two countries. This report highlights challenges addressed by the academies over many years that remain of current interest as the U.S., Russian, and other governments continue to cope with old and new forms of aggression that threaten the livelihood of populations at home and abroad.
Keywords: Conflict and Security Issues

Assessment of the SBIR and STTR Programs at the National Institutes of Health - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The National Institutes of Health (NIH) asked the National Academies of Sciences, Engineering, and Medicine to conduct a quadrennial review of its Small Business Innovation Research (SBIR) and Small Business Technology Transfer (STTR) programs, in accordance with a legislative mandate. Using quantitative and qualitative analyses of data, this report reviews the operations and outcomes stemming from NIH's SBIR/STTR awards. Drawing on published research and conducting new analyses based on both publicly available data and applicant data provided by NIH, Assessment of the SBIR and STTR Programs at the National Institutes of Health analyzes (1) the effectiveness of NIH's processes and procedures for selecting SBIR and STTR awardees; (2) the effectiveness of NIH's outreach to increase SBIR and STTR applications from small businesses that are new to the programs, from underrepresented states, and from woman-owned and minority-owned businesses; (3) collaborations between small businesses and research institutions resulting from the programs; and (4) a range of direct economic and health care impacts attributable to the programs.
Keywords: Policy for Science and Technology

Review of the SBIR and STTR Programs at the National Science Foundation - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The National Science Foundation (NSF) asked the National Academies of Sciences, Engineering, and Medicine to conduct a quadrennial review of the NSF Small Business Innovation Research (SBIR) and Small Business Technology Transfer (STTR) programs, in accordance with a legislative mandate. Drawing on published research plus existing data, Review of the SBIR and STTR Programs at the National Science Foundation analyzes the effectiveness of NSF award selection process and postaward assistance; the effectiveness of the STTR program in stimulating new collaborations; the economic and noneconomic impacts of the programs; effectiveness of the programs in stimulating technological innovation and supporting small, new firms across the technological spectrum; and the role of the programs in providing early capital to firms without other significant sources of support.
Keywords: Industry and Labor